The Preschool Child in Suka_ Village, North Sumatra III. Upper arm Circumference and Skinfolds as Indicators of Nutritional Status - Jane A. Kusin; H. S. R. Parlindungan Sinaga; J. Khoman; J. M. Houtkooper; U. Renqvist (Indonesian Pediatric Society, 1982)
Upper arm circumfereru:e, triceps and subscapular skinfolds were measured at 6-monthly intervals during one year in a group of preschool children, age 0 - 5 years.All 3 measurements decreased as compared with the reference in the age period 1 - 23 months followed by a catch-up at age 2- 4 years.The predictive value of upper arm circumference for the development af malnutrition was low. Age group 1 - 23 months should be considered